Optimal transition control between combustion modes in a Diesel-ignited gas engine. (April 2020) - Hutter, Richard; Hänggi, Severin; Albin, Thivaharan; Onder, Christopher H.
Abstract: Diesel-ignited gas engines show high emission of hydrocarbons at low load and thus have to be operated there in Diesel-only mode. The transition between the combustion modes typically results in a significant torque deviation as well as in additional tailpipe emissions of pollutants. This paper presents a study on the transition between the two combustion modes, namely Diesel-only mode and dual-fuel mode. Optimal actuator trajectories are derived by solving a nonlinear optimal control problem. With the optimized trajectories implemented in a feedforward controller, the transition is significantly improved in terms of torque deviation, cumulative nitrogen oxide emissions, as well as cumulative hydrocarbon emissions.